Homomorphisms between Fuzzy Approximation Spaces Based on Residuated Lattice - Yuan Zhao (Journal of Applied Mathematics)
Two kinds of homomorphisms of fuzzy approximation spaces based on complete residuated lattice are proposed. The homomorphisms are structure-preserving maps in some sense. We also introduce the fuzzy approximation subspaces and investigate their correspondence with the homomorphisms. Given a fuzzy equivalence relation, the factor set of the fuzzy approximation space is discussed.